COLLABORATIVE GOVERNANCE DALAM MELAKSANAKAN PROGRAM KAMPUNG KELUARGA BERENCANA MERANTI MANDIRI DI KELURAHAN MERANTI PANDAK KECAMATAN RUMBAI PESISIR KOTA PEKANBARU TAHUN 2020 - Dwi Arini Yusmandani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The high rate of population growth in Indonesia makes the government need to strengthen the Population, Family Planning and Family Development (KKBPK) program. Family Planning Village is one of the government's flagship programs in order to create quality small families. Kampung Keluarga Berencana is a regional unit that has certain criteria, where there is an integration of population programs, family planning, family development, and related sector development that is carried out systematically. The purpose of this study was to determine collaborative governance in the Meranti Mandiri Family Planning Village program, Meranti Pandak Village, Rumbai Pesisir District, Pekanbaru City in 2020 and to determine the factors that influence collaborative governance in the Meranti Mandiri Family Planning Village program, Meranti Pandak Village, Rumbai Pesisir District, Pekanbaru City in 2020. This research is a descriptive research with a qualitative approach. The location of this research was in the Meranti Mandiri Family Planning Village, Meranti Pandak Village, Rumbai Pesisir District, Pekanbaru City. Data collection techniques used is through interviews and documentation. Data analysis techniques used is data collection, analysis, description and conclusion. The research results show that Collaborative Governance in implementing the Meranti Mandiri Family Planning Village program in 2020 seen through stages the Face to face dialogue, Trust-building, Commitment to the process, Shared understanding and Intermediate outcomes well done. However, in the implementation of the Trust-building stage has not been maximized. This is because the program implementers do not understand the duties and functions of their field. Keywords: Collaborative Governance, Family Planning Village